Thinking critically while storytelling: Improving children’s HOTS and English oral competence - Setyarini, Sri; Muslim, Ahmad Bukhori; Rukmini, Dwi; Yuliasri, Issy; Mujianto, Yanuarius (Universitas Pendidikan Indonesia, 2018)
Although studies on the development of higher order thinking skills (HOTS) as part of Bloom’s revised taxonomy have grown significantly among adult learners, little is known about its use for teaching English to young learners. In the Indonesian context, HOTS is mandated by the scientific-based 2013 national curriculum. This study investigates the development of HOTS strategies and possible challenges through storytelling among seventh grade students to improve their speaking ability. This Classroom Action Research (CAR) obtains data from classroom observations, interviews with the teachers and students, and analysis of lesson plans. The findings reveal that, in its simple form, HOTS in storytelling was developed in young English learners through open-ended question, a strategy which enables students to practice speaking through giving opinion, comment, and imagination while analyzing and evaluating the story. However, due to their limited language competence and unfamiliarity with the story context, students still find difficulties in creating their own stories, the highest level of educational objective. The study finally comes up with ways to engage students in storytelling while developing their HOTS.